Examining customer perception of employee demographics and its effects on customer satisfaction: the case of HFC bank in Nairobi County - Muganda, Imelda (Strathmore University, 2020)
This study sought to establish how employee demographics can be utilized to satisfy the new, more extensive customer base being targeted by the commercial bank. The research specifically sought to examine the effects of service experience, personality factors, and employee educational attainment on customer satisfaction. The research was grounded on the tricomponent theory and human capital theory. A descriptive research design was adopted with the aim of determining the relationship between the research variables, with the unit of analysis being HFC Customers within Nairobi County. The population of the research was 59,926. The sample respondents were calculated using the Yamane formula. The sample size for the research was 397 respondents. Data were collected using structured questionnaires using the drop and pick technique. The research instrument was pretested among 10% of the sample respondents. Descriptive and inferential statistical methods were used in data analysis. The relationship of the variables was tested using regression analysis. The results of the investigation were presented graphically using bar graphs and tables. The study was able to obtain a 66% response rate. The findings indicate there is a positive correlation between employee service experience, employee personality factors, employee educational attainment, and customer satisfaction. The study established that 51.1% of the variations in customer satisfaction within the bank are determined by employee demographics. The study concludes that improving the competencies of the employees, their professional expertise, empathy in service provision, and educational attainment are vital to improving customer satisfaction. The study recommends that commercial banks should support employees through delegation of decision making, training opportunities, and professional development to support better customer experience within the bank.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Customer base; Marketing; Banking; Service experience